Religious Culture As A Strategy For Student Character Development In Pesantren - Eliza Yanti Yanti; Agus Salim Salabi (Afkaruna: International Journal of Islamic Studies (AIJIS), 2026)
The decline in student character, such as low discipline, responsibility, and religious attitudes, is a significant issue in education. One way to foster character building is through the implementation of religious culture within Islamic boarding schools (Islamic boarding schools). This study aims to analyze the implementation of religious culture as a strategy for developing student character at the Al-Zahra Modern Islamic Boarding School in Bireuen. This study employed a qualitative method with a field study approach. The research informants consisted of the head of the Islamic boarding school, teachers, caretakers, and students. Data collection techniques included interviews, observation, and documentation, while data analysis utilized data reduction, data presentation, and conclusion drawing. The results indicate that religious culture is implemented through the practice of daily worship, scheduled religious activities, educators' role models, and enforcement of Islamic boarding school regulations. Supporting factors include educator commitment, a religious environment, worship facilities, and parental cooperation. Inhibiting factors include differences in parental understanding, the diversity of student characters, and the influence of the environment outside the Islamic boarding school. The study concludes that the consistent implementation of religious culture can foster religious character, discipline, responsibility, and morals in students. This research contributes to the development of character education based on religious culture in modern Islamic boarding schools.